"My trip to Europe is about America rallying the world's democracies" and the elephant in NATO's room. Issue 2 (3rd April 2023) - Kollias, Christos; Tzeremes, Panayiotis
ABSTRACT: Using President Joe Biden's opinion article published in The Washington Post ahead of the June 14, 2021 NATO Summit as a point of departure, the present paper examines how NATO members fare in terms of the core constituent elements of liberal democracy such as civil liberties and freedom of expression. To this effect, the paper uses three indices constructed and published by the Varieties of Democracy project. The Liberal democracy, Civil liberties and Freedom of expression indices. The results from club convergence analysis that covers the post-Cold War period, indicate the presence of different convergence clubs among NATO's member-states and Turkey as the single divergent country. Moreover, given that many NATO countries are also EU members, the paper examines the comparative effect the dual NATO and EU membership had on the democratisation process of East European countries and Turkey. The findings suggest a statistically stronger impact of EU membership vis-à-vis NATO membership.